Evaluation of the Financial Results of the Organization - Gorelova N. S., Mishulina O. V. (Relevant issues of management, economics and economic security, 2022)
the importance of the financial results of the activity of the business entity increases in conditions of market relations and economic independence and, as a result, the role of integrated economic analysis increases, which makes it possible to identify reserves for increasing the efficiency of economic activity, to assess its financial results. The study shows the comprehensive analysis methodology and approach to evaluating the financial results of the organization's economic activity. General scientific and unique economic analysis methods of the organization's financial activities were used for the study. The result of the study was scientifically substantiated directions for improving the economic activities of the organization, necessary to increase its financial results.
Keywords: организация; рентабельность; экономическая деятельность; economic activity; profitability; валовая прибыль; чистая прибыль; операционный и финансовый рычаги; organization; gross profit; net profit; operational and financial leverage